Pharma-Ecology, 2nd Edition - Jjemba, Patrick (Wiley, 2018)
The revised edition of the guide to environmental impact of pharmaceuticals and personal care products The revised and updated second edition of Pharma-Ecology joins the health and environmental sciences professions' concern over the occurrence and fate of pharmaceutical and personal care products (PPCPs) in the environment and explores how to best minimize their impact. The text highlights the biological effects of various classes of pharmaceutical compounds under clinical settings, their modes of action, and approximate quantities consumed. The second edition contains the most recent knowledge about the ecological impact of PPCPs as more sensitive detection techniques have become available, since the book was first published. The second edition offers the most up-to-date information on pharma ecology and bridges the gap between medicine, public health, and environmental science. This new edition contains helpful learning objectives for each chapter, as well as a brief section at the end of each chapter that presents a set of open ended questions. This vital resource: • Explores the biological effects of pharmaceutical compounds under clinical settings, their modes of action, approximate quantities consumed • Provides researchers and scientists with critical background data on the environmental impacts of PPCPs • Contains the most current information on PPCPs' ecological impacts, based on new detection techniques • Bridges the gap between medicine, public health, and environmental science Written for ecologists, engineers, microbiologists, pharmacists, toxicologists, chemists, physicians, and veterinarians involved in pollution and environmental analysis, the second edition of Pharma-Ecology contains the most current information available on the environmental impact of pharmaceuticals and personal care products.